The mathematical model and the method of temperature calculation at nodes of dump truck BelAZ traction drive’s EDP-800 collector-brush assembly in stationary mode - V. V. Kharlamov; S. N. Nayden; A. S. Khloptsov; P. G. Petrov (Омский научный вестник)
The article presents a mathematical model of a dump truck BelAZ traction drive’s EDP-800collector-brush assembly and the calculation of temperature rised in stationary mode. Using thermoimaging the temperature points at the nodes of the collector-brush assembly for nominal operation of the engine are obtained. The estimation of the mathematical model is done by comparison of experimental and calculated data.